Municipal bonds in sub-Saharan Africa: the checkered past of debt instruments in an era of incomplete decentralization - Gorelick, Jeremy (Department of Environmental and Geographical Science, 2020)
Cities across sub-Saharan Africa are faced with challenges in urban planning and service delivery due to insufficient capital for long-term investment projects. Despite the success of municipal bonds as a tool to assist in closing this financing gap in much of the rest of the world, there have been limited examples of success in this region. This study looks at the universal obstacles limiting sub-national governments from using municipal bonds as a financial instrument before examining four case studies - Johannesburg, Douala, Dakar and Kampala - to better understand their approaches to municipal bond issuance. Based on the findings from research, the thesis concludes that the chief obstacle blocking the uptake of municipal bond issuance as a means for raising funds stems from a variety of elements in the constitutional and regulatory systems in each country. This represents a significant departure from the commonly-held understandings that cities in the region are not eligible for long-term debt and are ill-managed, lack capacity, or are not viewed as creditworthy by institutional investors and other purchasers of municipal bonds. The success of municipal bond issuance appears to be contingent on strong interlinkages between central and subnational governments. This dissertation offers a critical review of the explicit and implicit powers granted to local governments under the constitutions of each of the countries, specifically the legislation that enables or prohibits municipalities from issuing bonds. Reform to the existing regulatory and legal environments across the African continent, ones that govern a financially-sustainable level of indebtedness for sub-sovereign governments, is an essential step in ensuring the future growth of Africa’s cities.